2001
DOI: 10.1577/1548-8675(2001)021<0022:shokrw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Spawning Habitat of Kootenai River White Sturgeon, Post-Libby Dam

Abstract: The Kootenai River white sturgeon Acipenser transmontanus has been isolated from other white sturgeon populations for over 10,000 years, Bonnington Falls in British Columbia, Canada, creating the isolation. Libby Dam, constructed in 1972, modified the flow and temperature regime of the river, which affected spawning and recruitment of white sturgeon. Kootenai River white sturgeon are only known to spawn in a reach near Bonners Ferry, Idaho, 100 km downstream from the dam. In 2 of 8 years of study, only 15 whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 26 publications
1
71
0
1
Order By: Relevance
“…Eggs naturally deposited on substrate egg mats have been used to locate and describe spawning habitat for many sturgeon species (e.g., Fox et al 2000;Paragamian et al 2001;Duncan et al 2004); however, only a single study has produced estimates of total egg deposition using this sampling gear. Sulak and Clugston (1998) estimated that total deposition of Gulf sturgeon eggs in the Suwannee River, Florida, ranged between 404,600 and 711,000 eggs/spawning event.…”
Section: Discussionmentioning
confidence: 99%
“…Eggs naturally deposited on substrate egg mats have been used to locate and describe spawning habitat for many sturgeon species (e.g., Fox et al 2000;Paragamian et al 2001;Duncan et al 2004); however, only a single study has produced estimates of total egg deposition using this sampling gear. Sulak and Clugston (1998) estimated that total deposition of Gulf sturgeon eggs in the Suwannee River, Florida, ranged between 404,600 and 711,000 eggs/spawning event.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no clear understanding of the cause of recruitment failure; however, there is consensus that river regulation is a significant contributing factor (McAdam et al 2005;Paragamian et al 2001Paragamian et al ,2009). …”
Section: Whole-body Glycogen Concentration Versus (A) Days Post Hatmentioning
confidence: 99%
“…Several studies including McAdam et al (2005), McAdam (2011), and Paragamian et al (2001 have suggested that suitable spawning and larval incubation habitat used by sturgeon may be negatively impacted by river regulation, limiting survival, leading to recruitment failure.…”
Section: Whole-body Glycogen Concentration Versus (A) Days Post Hatmentioning
confidence: 99%
“…It not only provides food and recreation for humans, but also maintains a healthy ecological balance in the flora and fauna of riparian habitats. Due to construction and operation of a dam, the natural fluctuations in the stream water are no longer available which reduces the required areas for fish to grow and reproduce, and even to hide from predators (King et al 2015;Waters et al 2015;National Fish Habitat Action Plan 2009;Null and Lund 2012;Piman et al 2013;Jager and Smith 2008;Paragamian et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…After the completion of Libby dam on the Kootenai River in 1972, the white sturgeon population became isolated and distinct in the Columbia River basin (McDonald et al 2010;Paragamian et al 2001;Setter and Brannon 1990). The white sturgeons in the Kootenai River became listed as an endangered species in 1994 (USFWS 1994).…”
Section: Introductionmentioning
confidence: 99%